ISMOIL GASPRINSKY AND NEW METHOD SCHOOLS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article extensively analyzes the role of Ismayl Gasprinsky in the Jadid movement, his enlightened views, and his contribution to the education system of the Turkic peoples through the New Method schools. Gasprinsky's motto "Unity of language, unity of thought, unity of work", the activities of the "Tarjimon" newspaper, and the process of the spread of New Method schools in Turkestan and other countries are studied.